Tinjauan Literatur: Strategi Peningkatan Aksesibilitas Layanan bagi Mahasiswa Penyandang Disabilitas di Perpustakaan Perguruan Tinggi - Jeni Sarah Amalia; Elva Rahmah (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
College libraries play a vital role in supporting the educational process, many challenges exist in providing equal access to services for students with disabilities. This study aims to develop a comprehensive strategy to enhance the accessibility of library services, thereby optimizing academic support for students with disabilities and improving national standards for university libraries. The method used was a literature review, focusing on a synthesis analysis of 15 selected articles published between 2017 and 2024. The results indicate that physical, digital, and institutional barriers remain substantial and fall short of international standards, such as those established by the International Federation of Library Associations and Institutions (IFLA). Existing services are often fragmented, inconsistent, and constrained by limited resources, including funding and technology, as well as unstructured policies. In conclusion, the accessibility of university library services for students with disabilities remains low and suboptimal, rendering the available resources difficult to access and utilize effectively, and resulting in a high dependency on assistance from others or volunteers.